Introduction to civil engineering through the PLAXIS application in construction planning for students of SMAN 3 Jakarta - Ruwaida Zayadi; Muhammad Zaki; Ulfa Fatmasari Faisal; Lilik Kusumawati; Salwa Zahra Rizkina (Community Empowerment, 2024)
Infrastructure development is one of the important pillars in the progress of a nation. In infrastructure development, the role of Civil Engineering is very vital. In this modern era, the need for experts in the field of Civil Engineering is increasing. Therefore, it is important for high school students to know and have basic knowledge about Civil Engineering as a future profession of choice. This PKM program activity aims to increase the knowledge and interest of SMAN 3 Jakarta students in the Civil Engineering Engineer profession through the application of the PLAXIS application in construction planning. The method used was a demonstration of the use of the PLAXIS application and distributing questionnaires to students. The results of the introduction show that students show a significant increase in understanding of the Civil Engineering Engineer profession and an increased interest in the field of Civil Engineering. This is proven by the results of the questionnaire distributed to 25 student participants, showing that 64% of students were quite interested and 28% of students were interested in continuing to study the PLAXIS application. Meanwhile 54% of students are quite interested and 44% of students are interested in the profession of Civil Engineering Engineer.